2001
DOI: 10.2165/00007256-200131120-00003
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Fitness, Health Outcomes and Quality of Life

Abstract: The health benefits and quality-of-life outcomes of a fit musculoskeletal system (musculoskeletal fitness) are reviewed in this article. The World Health Organization suggests health is a state of complete physical, mental or social well-being and not merely the absence of disease or infirmity. Physical health includes such characteristics as body size and shape, sensory acuity, susceptibility to disease and disorders, body functioning, recuperative ability and the ability to perform certain tasks. One aspect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
2
30

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(153 citation statements)
references
References 91 publications
5
116
2
30
Order By: Relevance
“…In agreement with these results, several previous studies, in healthy and diseased groups, have demonstrated beneficial effects of physical activity on several quality of life and mental health parameters 7,8,20,21,22 . Pilates exercise could be an alternative strategy for promoting health status and quality of life improvements in both nonclinical and clinical populations 23,24,25,26,27 .…”
Section: Effects Of Physical Exercise On Quality Of Lifesupporting
confidence: 89%
“…In agreement with these results, several previous studies, in healthy and diseased groups, have demonstrated beneficial effects of physical activity on several quality of life and mental health parameters 7,8,20,21,22 . Pilates exercise could be an alternative strategy for promoting health status and quality of life improvements in both nonclinical and clinical populations 23,24,25,26,27 .…”
Section: Effects Of Physical Exercise On Quality Of Lifesupporting
confidence: 89%
“…Only participants with complete data were included in analyses. Restricted linear splines (10,50, 90 percentiles) were tested in all analyses to account for non-linear associations of sitting time. Fit was compared using an F-test.…”
Section: Resultsmentioning
confidence: 99%
“…Poor cardiorespiratory fitness is a strong risk factor for morbidity and premature mortality, especially of cardiovascular origin, among adults (8). Muscular fitness, ie, muscular power, strength and endurance, is related to musculoskeletal morbidity, eg, low-back pain, but is also considered important for hormonal and substrate metabolism, particularly for insulin sensitivity of active skeletal muscles (9), and is related to premature mortality among adults (10). Adverse associations of sedentary behaviors have been identified with cardiorespiratory and muscular fitness among children and young adults (11,12), and with muscular fitness among the elderly (13).…”
mentioning
confidence: 99%
“…Entretanto, ainda não existem evidências científicas que suportem a afirmação que os alongamentos realizados antes e/ou após exercícios previnem lesões esportivas, mas estes não são desaconselháveis (20) . Porém, é inegável a associação da flexibilidade e da atividade física com a melhora da qualidade de vida (1) . A implementação clínica do calor é sugerida por aumentar a extensibilidade das fibras do colágeno e as propriedades mecânicas do mús-culo (10) .…”
Section: Discussionunclassified
“…Flexibilidade adequada é uma característica importante de aptidão física, sendo um componente fundamental para a qualidade de vida (1) , performance esportiva, prevenção e reabilitação de lesões (2) . Exercícios com finalidade de aumentar a força e a capacidade aeróbica diminuem a flexibilidade muscular e este efeito pode levar a risco aumentado de lesões durante os treinamentos, competições e/ou participação em atividades físicas diárias (2) .…”
Section: Introductionunclassified